2017
DOI: 10.1515/prolas-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Optotype Structure for Monitoring Visual Acuity

Abstract: Communicated by Ivars Lâcis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Letter optotypes are also essential in these charts, reducing the study's reliability. [20][21][22] The screens of computer monitors and smartphones have respective pixel sizes and brightness required for reliable visual acuity test. Thus, using ICP should provide accurate enough VA measurement at any distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Letter optotypes are also essential in these charts, reducing the study's reliability. [20][21][22] The screens of computer monitors and smartphones have respective pixel sizes and brightness required for reliable visual acuity test. Thus, using ICP should provide accurate enough VA measurement at any distance.…”
Section: Discussionmentioning
confidence: 99%
“…These stimuli' stripes' length is extended by approximately 20% compared with the standard triple optotype to ensure the indistinguishability of near-edge stimuli by indirect signs of blurred spot orientation. [20][21][22] The VA test using a computer program was performed using "E" optotype oriented in 4 ways. Intermediate VA was assessed at 60 cm away from the subject's eye after PanOptix implantation and 80 cm away from the eye after AT LISA tri implantation.…”
Section: Interactive Computer Program (Icp) Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that meridional amblyopia in children can be found associated with hyperopic astigmatism [94][95][96], whereas others reported that children with hyperopic astigmatism showed no meridional amblyopia, but did show reduced acuity for both grating orientations [89,97]. These contradictions have been attributed to the fact that the studies vary in methodologies and criteria used for visual acuity assessment [91,98,99]. These factors cause differences not only in meridional visual acuity, but also in results of any other visual acuity measurement methods [99,100].…”
Section: Diagnosing Meridional Amblyopia In Astigmats On the Basis Of Assessment Of Asymmetries In Visual Acuity And Refraction As Vectormentioning
confidence: 99%
“…These selective criteria include such visual perception threshold characteristics as minimum perceptible, minimum visible, mini¬mum resolvable, minimum separable, minimum discrim¬inable, minimum deformable, etc. It should be noted that these criteria are fundamentally different from each other and characterize the state of various visual acuity mechanisms[98,99, 101,104,105]. Thus, minimum visible characterizes the ability to note the presence of an object; minimum perceptible characterizes the ability to note the presence a threshold contrast; minimum separable or minimum resolvable acuity characterizes the ability to distinguish among the details of the object structure; and minimum perceptible allows assessing the shape of a pattern through its contour.…”
mentioning
confidence: 99%